Scientific Evidence and Its Admissibility in Syariah Court: Legal Analysis of Syariah Court Evidence Law: (Bukti Saintifik dan Penerimaannya di Mahkamah Syariah: Analisis Perundangan bagi Undang-Undang Keterangan Mahkamah Syariah) (Kanun: Jurnal Undang-undang Malaysia, 2020)
Presenting scientific evidence in court is significant to prove and convict a case, as well as to exonerate innocent people. Acceptance of scientific evidence has been practiced in the civil courts as early as the 1950s and is widely adopted today. However, the scenario is different in the syariah courts, where scientific evidence is rarely used. In fact, Syariah Court Evidence law contains provisions pertaining to scientific evidence that are in pari materia to the Evidence Act 1950. Therefore, this paper aims to examine the provisions in Syariah Court Evidence law regarding scientificevidence and its acceptance in the Syariah Court. This qualitative study uses documentary research methods in collecting primary and secondary e content analysis method by adopting inductive reasoning. The results of the study show that scientific evidence can be presented by forensic experts. The hukum syarak (sharia law) accepts scientific evidence as one of the means of proving or disproving. In addition, the syariah court's Evidence Law also paves the way for the acceptance of scientific evidence through provisions concerning public documents and expert opinions. There are also legal procedures regarding scientific evidence. In conclusion, sharia law has accepted forensic science for over a thousand years before it was introduced using more scientific and modern names, terms, and concepts. This study focuses on the evidence law, as well as clarifying the opinions of experts that have not yet been examined in previous studies. This study also provides a thorough understanding of the concept of forensic science in the context of the evidence law of the syariah courts.Keywords: Fiqh forensics, forensic science, evidence law, syariah courts, scientific evidence